CHALLENGES AND IMPORTANCE OF FOOD SAFETY MANAGEMENT IN HOSPITALITY INDUSTRY - Mastilović, Jasna S; Vukotić, Jovan R; Ćerović, Slobodan R (Food and Feed Research, 2024)
A survey of the degree of importance consumers attach to the food safety managment in accomodation facilities offering food was carried out. Consumers, that is, potential guests, without exception, attach importance to food safety comparable to the importance they attach to sensory properties of food, nutritional value of food and efficiency of service, which from the aspect of business success further emphasizes the need for transparent management of food safety in accomodation facilities offering food. With the aim of comparing the complexity, challenges and importance of food safety management in accomodation facilities that provide combined tourist accommodation and catering services depending on the type of facility, analysis of the complexity of food safety issues was performed depending on the type of facility. The obtained results suggest that the complexity of food safety management depends on the type of facility and is most pronounced in facilities such as hotels and motels. For the case of accomodation facilities with complex food offer, such as hotels, the challenges of food safety were considered through interviews with responsible staff in hotels. The challenges of managing food safety in these facilities are numerous and conditioned by various factors, starting from the diversity of the raw materials, through the compactness of the space, to the challenges related to the establishment of a traceability system. In the complex environment of food safety management in hotels, the knowledge of staff is invaluable.
Keywords: food, safety, management, hospitality industry